The New Keynesian Phillips curve tested on OECD panel data - Roger Bjørnstad; Ragnar Nymoen (Kiel Institute for the World Economy (IfW), 2008)
In their work, Galí, Gertler and Lopez-Salido, GGL, assert that the hybrid New Keynesian Phillips curve (NPC) with dominance of forward-looking behavior and real marginal costs is robust to choices of estimation procedure, details of variables definitions and choice of data samples. In an estimation on panel data from OECD countries we replicate the typical empirical NPC from country studies. However, we also test an alternative economic interpretation of the empirical correlations. Specifically we find that the expected rate of future inflation and real marginal costs serve as replacements for equilibrium correction terms that are implied by the general imperfect competition model of wage and price setting. As a explanatory model of OECD inflation, the NPC is encompassed by an existing theory.
Keywords: E12; C52; C23; E31; 330; New Keynesian Phillips Curve; forward-looking price setting; panel data model; encompassing